2017
DOI: 10.7150/thno.16677
|View full text |Cite
|
Sign up to set email alerts
|

Dual-targeted and pH-sensitive Doxorubicin Prodrug-Microbubble Complex with Ultrasound for Tumor Treatment

Abstract: In this study, we investigated the potential of a dual-targeted pH-sensitive doxorubicin prodrug-microbubble complex (DPMC) in ultrasound (US)-assisted antitumor therapy. The doxorubicin prodrug (DP) consists of a succinylated-heparin carrier conjugated with doxorubicin (DOX) via hydrazone linkage and decorated with dual targeting ligands, folate and cRGD peptide. Combination of microbubble (MB) and DP, generated via avidin-biotin binding, promoted intracellular accumulation and improved therapeutic efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…[7][8][9][10][11][12] The ultrasound (US)-controlled release of chemotherapeutics by microbubbles (MBs) has become a promising therapeutic approach for drug delivery to treat malignant tumors. [16][17][18][19][20][21] In this strategy, chemotherapeutics are incorporated into MB shells by hydrophobic interactions, or attached to MB shells by various approaches, such as nanoparticles. [20][21][22][23][24] Thereafter, the MB-loaded chemotherapeutics are then released from MBs that flow through the targeted tumor tissues by high-intensity focused US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] The ultrasound (US)-controlled release of chemotherapeutics by microbubbles (MBs) has become a promising therapeutic approach for drug delivery to treat malignant tumors. [16][17][18][19][20][21] In this strategy, chemotherapeutics are incorporated into MB shells by hydrophobic interactions, or attached to MB shells by various approaches, such as nanoparticles. [20][21][22][23][24] Thereafter, the MB-loaded chemotherapeutics are then released from MBs that flow through the targeted tumor tissues by high-intensity focused US.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Although liposome-microbubble complexes have improved the targeted tumor delivery and accumulation of chemotherapeutic drugs, the role of ICD in this process has not been elucidated. [16][17][18][19][20][21] In this study, we constructed a liposome-MB complex in which doxorubicin (Dox, an ICD inducer) was encapsulated in a liposome (Dox-liposome) and attached to the lipid shell of MBs via avidin-biotin linkage. Thereafter, we detected the efficacy of US-triggered drug delivery from these complexes in LL/ 2c and CT26 tumor models, and focused on the comparative effects of the respective drug preparations as well as the levels of ICD that they provoked.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the anti-tumor efficacy of resveratrol on tumor-bearing mice was significantly enhanced. With ultrasound coordination, Luo et al 43 devised pH-sensitivemicrobubble complex, which consists of a succinylatedheparin carrier combined with Dox through hydrazone linkage and conjugated with dual targeting ligands through biotin-avidin binding ( Figure 4A). In particular, the pHsensitive nanoparticles attained high tumor inhibition rates in the experiment of inhibiting cell proliferation, inducing apoptosis and anti-tumor angiogenesis, providing an effective strategy for targeting drug delivery and ultrasound imaging ( Figure 4B and C).…”
Section: Ph-sensitive Ultrasound Contrast Agentmentioning
confidence: 99%
“…The release manners of SFN and CCM from LAC-SFN /CCM-NPs, LAC-SFN-NPs, LAC-CCM-NPs, and SFN/ CCM-NPs were examined using dialysis method. 38 Briefly, samples were dissolved in phosphate-buffered saline solution (PBS, 5 mL, pH 5.5 or 7.4) and sealed separately in dialysis bags. Samples were dialyzed against 50 mL corresponding buffers, which were incubated in a 37°C water bath under constant shaking (100 rpm).…”
Section: In Vitro Release Of Nanoparticlesmentioning
confidence: 99%